2018
DOI: 10.6007/ijarafms/v8-i2/4239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electronic Customer Relationship Management on Electronic Service Quality Provided by the Commercial Banks in Kuwait

Abstract: The study aims to investigate the impact of electronic customer relationship management on Electronic service quality provided by the commercial banks in Kuwait. The study population consisted of all of the customers of the commercial banks in Kuwait. A convenience sampling was taken from customers of the commercial banks in Kuwait and using the electronic services provided by banks that estimated (541) respondents. To achieve the objectives of the study, the descriptive analytical method was used through A qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 29 publications
3
26
0
1
Order By: Relevance
“…These platforms help organizations sense and respond to customers' dynamic needs and expectations and to sustain deep and long-term relationships. Furthermore, these results also agree with those of recent research (Aldaihani & Ali, 2018;Chierici et al, 2018;Latuny, 2018;Wang & Kim, 2017) showing the contribution of SCRM usage to improving CRM processes and organizational performance as a whole.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These platforms help organizations sense and respond to customers' dynamic needs and expectations and to sustain deep and long-term relationships. Furthermore, these results also agree with those of recent research (Aldaihani & Ali, 2018;Chierici et al, 2018;Latuny, 2018;Wang & Kim, 2017) showing the contribution of SCRM usage to improving CRM processes and organizational performance as a whole.…”
Section: Discussionsupporting
confidence: 92%
“…The population was the banking industry. Entrepreneurship is an urgent part of today's banking industry in light of the current dynamic and active business environment (Aldaihani & Ali, 2018;Chai & Entebang, 2013;Ijeoma & Onuoha, 2018). Furthermore, recent research (Aldaihani & Ali, 2018;Hallikainen et al, 2017) has suggested that banks that have an entrepreneurial orientation should place more emphasis on the use of SCRM systems to enhance CRM processes.…”
Section: Sampling and Questionnaire Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relationship marketing is a business philosophy developed from the need to maintain a committed current customer base for the organization which involves strengthening relationships with current customers and retaining them rather than seeking new customers (Ojiaku et al, 2017). Another opinion says that relationship marketing will create strengthening and maintaining strong relationships with customers and stakeholders (Aldaihani & Ali, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%